A smoothing test under first-order autoregressive processes and a first-order moving-average correction - Ana Paula Martins (Economics and Econometrics Research Institute (EERI), 2016)
This paper focuses on two applications of time series methods. The first proposes a simple transformation of the unit root form of stationary testing to infer about the validity of smoothing by second-order running averages of a series, or of the variables in a linear model (here opposing co-integration testing). The second one advances a simple iterative algorithm to correct for MA(1) autocorrelation of the residuals of the general linear model, not requiring the estimation of the error process parameter.
Keywords: C22; C12; C13; 330; Smoothing Tests under First Order Autoregressive Processes; Running Averages; Negative Unit Roots; Moving Average Autocorrelation Correction in Linear Models